Knowledgment of Birth Spacing Among Women Attending Primary Health Care Centers in Mukalla District, Yemen - Saeed Abaddan, Najla; Saleh Sayad, Asrar; I Alezzi , Jalil (Diyala Journal of Medicine, 2023)
Background: Short birth spacing linked with adversative health consequences for infant, child and maternal mortality also increases the chances of mother and their children survival. Objective: To assess the determinants and the knowledge of birth space amongst women of reproductive age in Mukalla district, Hadhramout Governorate, Yemen. Patients and Methods: A cross sectional study of 384 women of multiplicative ages (15-49 years) was conducted at primary health care centres in Mukalla district. The study was conducted from November. 2018 to Oct 2019. Results: The median birth spacing was 35 months. (50.8 %) of respondents have been committed undersized birth spacing underneath the indorsed interval of ideal delivery spacing. Multivariate logestic V regression revealed that age of mother between 15-24 years (OR 3.255, 95%CI 1.598-6.629, P=0.001), not enough family income (OR 1.867, 95%CI1.104-3.158, P =0.020 ), number of living children ≤ 3 children (OR 1.225, 95%CI .532–2.520, P=0.027) and breast feeding duration < 6 months (OR7.435 , 95%CI 1.490 – 37.101,P=0.014) or 6-<12 months (OR 7.320, 95%CI 1.406–38.116, P=0.018) were linked with augmented hazard of short birth spacing, whereas mother’s history of chronic disease (OR.026,95%CI .003-.227,P=.001) and modern family planning methods utilization (OR.208, 95%CI.112-.386, P=0.000) were linked with decreased risk of little birth space. (58.1%) of respondents had high level of knowledge about the birth spacing. Conclusion: Certain factors were significant predictors of short birth spacing in Mukalla's women. This should lead to encouragement of longer birth spacing between births.